2020
DOI: 10.1210/clinem/dgz310
|View full text |Cite|
|
Sign up to set email alerts
|

Once-Weekly Somapacitan vs Daily GH in Children With GH Deficiency: Results From a Randomized Phase 2 Trial

Abstract: Context Daily growth hormone (GH) injections can be burdensome for patients and carers. Somapacitan is a long-acting, reversible albumin-binding GH derivative in development for once-weekly administration in patients with growth hormone deficiency (GHD). Objective The objective of this study is to evaluate the efficacy, safety, and tolerability of once-weekly somapacitan vs once-daily GH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 21 publications
4
67
0
Order By: Relevance
“…The safety of somapacitan was further confirmed by results from the global phase 3 trial REAL 1, in which the overall safety and efficacy of somapacitan was found to be similar to daily GH in treatment‐naïve patients with AGHD 12 . In addition, somapacitan was found to have similar efficacy to daily GH in a phase 2 trial in children with GHD 13 . However, the efficacy in previously GH‐treated patients with AGHD switching from daily GH to once‐weekly somapacitan has not previously been investigated.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The safety of somapacitan was further confirmed by results from the global phase 3 trial REAL 1, in which the overall safety and efficacy of somapacitan was found to be similar to daily GH in treatment‐naïve patients with AGHD 12 . In addition, somapacitan was found to have similar efficacy to daily GH in a phase 2 trial in children with GHD 13 . However, the efficacy in previously GH‐treated patients with AGHD switching from daily GH to once‐weekly somapacitan has not previously been investigated.…”
Section: Introductionmentioning
confidence: 78%
“…This may account for the slightly higher number of transient elevations in IGF‐I SDS to above +2 in the somapacitan‐treated patients. However, pharmacokinetic/pharmacodynamic modelling has shown that average IGF‐I levels over 1 week after dose titration are predicted to be similar between somapacitan and daily GH 13 . For the majority of patients in both treatment arms, IGF‐I SDS was below +2 for the duration of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…The most easily measured indicator of the effectiveness of a GH therapy in children is linear growth; the evaluation of response during the first year (ie, catch-up growth) appears to be most important for prediction models calculating final height ( 21-23 ). In a Phase 2 study, mean AHV for the somapacitan 0.16 mg/kg/week group was 12.9 cm/year compared to 11.4 cm/year with daily somatropin 0.034 mg/kg/day at week 26 (not significantly different), with comparable safety ( 24 ). Somatrogon demonstrated noninferior AHV compared to daily somatropin (10.10 cm/year vs 9.78 cm/year) with a similar safety profile in a Phase 3 study ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… 15 However, the frequency of preference for r‐hGH injection schedule in treating patients with GHD is not a clear concern, as currently only daily type is commercially available for treatment. 16 , 17 , 18 Patient preference research allows identification of the preferences for various treatment options and potential trade‐offs that participants are willing to make. 19 Patient preference for treatment is an essential dimension of health care that should be incorporated into decision making.…”
mentioning
confidence: 99%